1998
DOI: 10.1080/1354060980040108
|View full text |Cite
|
Sign up to set email alerts
|

Creating the Conditions for Classroom and Teacher Development

Abstract: The research on 'classroom conditions' reported in this paper forms a strand of the research and development activities undertaken as part of the 'Improving the Quality of Education for All' (IQEA) school improvement project. The 'IQEA approach' to school improvement emphasises the importance of enhancing the internal conditions of the school whilst undertaking innovations in curriculum and instruction in the pursuit of enhanced levels of student achievement. The rationale for the emphasis on 'internal conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…There is an absence of debate on political, economic and cultural trends with implications for capacity building. This has led to claims that the concept lacks clarity and articulation (Hadfield, Chapman, Curryer & Barrett, 2004;Hopkins, Beresford & West, 1998). As such, this research provides a valuable lens for taking a fresh look at what schools do to meet challenges of building capacity and improvement in productive ways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an absence of debate on political, economic and cultural trends with implications for capacity building. This has led to claims that the concept lacks clarity and articulation (Hadfield, Chapman, Curryer & Barrett, 2004;Hopkins, Beresford & West, 1998). As such, this research provides a valuable lens for taking a fresh look at what schools do to meet challenges of building capacity and improvement in productive ways.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 Conclusion Capacity building for school improvement is a difficult concept to define. Hopkins et al (1998) define it as enabling conditions that allow process to affect product. Fullan (2005) suggests the construct relates to development of collective ability to act together to bring about change.…”
Section: Discussionmentioning
confidence: 99%
“…Alexander (1992) has illustrated how imposing new practices on teachers without a parallel exploration and assimilation of underpinning rationales leads to changed practice but not necessarily improved practice. Hopkins et al (1998) come at this from a somewhat different direction when they claim on the basis of their development and research work in changing practice that, unless a school-improvement strategy reflects the implicit theories of practitioners, then it is 'doomed to failure' (p. 118). Connelly et al (1997) support both sets of conclusions when they claim from their own study that 'teachers are not mere screens who translate others' intentions and ideologies into practice.…”
Section: The Pupil-learning Dimensionmentioning
confidence: 96%
“…Research literature on teachers' collaboration and reflective practices has shown that professional exchange about teaching can boost professional development where as its absence can have a negative effect (Arthur et al 2010;Beresford and West 1998;Brady 2009;Bryk et al 1999;Butler et al 2004;Conner 2004;Day, Hadfield and Kellow 2002;Huntley 2005;Hopkins and Stern 1996;Hopkins, Naysmith and Palma 1998;Jolliffe and Hutchinson 2007;Lieberman 2009;McCotter 2001;Minnet 2003;Priestley and Sime 2005;Sarsar 2008;Saunders 2005;Talbert and McLaughlin 2002;Wilson 2008). With this study, I explored further why reflection on practice which remains private can have a limiting effect on professional development.…”
mentioning
confidence: 87%